The Implementation of Teleconsultation in Interprofessional Collaboration for Emergencies in Primary Care Facilities - Handi, Andrew (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Teleconsultation has become a crucial innovation in healthcare services, particularly in interprofessional collaboration for managing emergencies in primary healthcare facilities. This technology enables faster and more efficient communication among medical personnel, improving service quality and expediting clinical decision-making. This study aims to evaluate the effectiveness of teleconsultation implementation in interprofessional collaboration for emergency management in primary healthcare facilities and to identify challenges and solutions in its implementation. This research employs a descriptive approach with a mixed-methods design. Data were collected through in-depth interviews with healthcare professionals, observations of teleconsultation processes, and analysis of medical records of patients who received teleconsultation services during emergencies. The findings indicate that teleconsultation enhances communication efficiency among healthcare professionals, accelerates the diagnostic process and clinical decision-making, and reduces patient referral delays. However, challenges such as limited technological infrastructure, insufficient medical staff training, and difficulties in integrating information systems were identified. Teleconsultation has the potential to be an effective solution in improving emergency management in primary healthcare facilities, particularly within interprofessional collaboration. Enhancing technological infrastructure, providing adequate training for healthcare professionals, and optimizing referral systems are necessary to support the effective implementation of teleconsultation